Literature Review on the Impact of Social Media on Social Interaction in Schools - Utami, Patrisia Rahayu (Universitas Tanjungpura, 2024)
This literature study examines the influence of social media on social interactions in schools by collecting and analyzing various studies conducted by previous researchers. With the increasing use of social media among students, it is important to understand how social media influences school interactions by focusing on positive and negative effects. The findings from this study show that social media can influence social interactions at school in both positive and negative ways. On the one hand, social media makes communication between students easier and maintains their relationships both outside of school and at school. On the other hand, studies also identify negative impacts such as the emergence of anti-social attitudes due to excessive use of social media. Based on the results of the literature review, it is necessary to take a holistic approach to understanding the influence of social media on social interactions in schools. The lack of research on the impact of social media on social interactions in schools requires further research to explore effective strategies for managing social media use and identify best practices that can support healthy social interactions in the digital era.